2007
DOI: 10.1007/s00027-007-0881-6
|View full text |Cite
|
Sign up to set email alerts
|

Photochemincal processes involving nitrite in surface water samples

Abstract: A study into nitrite photochemistry was carried out on surface (both lake and river) water samples. In the tested samples, nitrite photolysis accounted for 0-60 % of • OH photoproduction, nitrate for 0-40 %, and dissolved organic matter (DOM) photochemistry played on average the main role. In real surface waters, an effect of radiation extinction by the water column would also be observed, and is expected to inhibit nitrate photochemistry at a higher extent compared to nitrite or DOM. Nitrite showed a defi nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 45 publications
3
107
2
3
Order By: Relevance
“…The shape of the curve indicates that 2N4CP was also degraded, thus the observed 5×10 −10 M increase from 21 June to 5 July would probably make 6×10 −10 M without degradation. Also note that in a whole summer sunny day the sunlight energy reaching the ground would be equivalent to about 10 hour (3.6×10 4 s) continuous illumination at 22 W m −2 UV irradiance (Minero et al 2007b (2 weeks) is just an approximation because of a sampling frequency bias, there is a clear disagreement between the field data and the calculation results. However, it should be considered that the water of the paddy fields also contains 13 mg C L −1 Non-Purgeable Organic Carbon (NPOC), and 3.1 mM bicarbonate.…”
Section: Resultsmentioning
confidence: 99%
“…The shape of the curve indicates that 2N4CP was also degraded, thus the observed 5×10 −10 M increase from 21 June to 5 July would probably make 6×10 −10 M without degradation. Also note that in a whole summer sunny day the sunlight energy reaching the ground would be equivalent to about 10 hour (3.6×10 4 s) continuous illumination at 22 W m −2 UV irradiance (Minero et al 2007b (2 weeks) is just an approximation because of a sampling frequency bias, there is a clear disagreement between the field data and the calculation results. However, it should be considered that the water of the paddy fields also contains 13 mg C L −1 Non-Purgeable Organic Carbon (NPOC), and 3.1 mM bicarbonate.…”
Section: Resultsmentioning
confidence: 99%
“…The free radicals sources include: (i) Photolysis of NO 2 -and NO 3 -ions to •OH (Vione et al, 2006;Minero et al, 2007); (ii) Generation of free radical species such as superoxide ion (O 2 -), hydrogen peroxide (H 2 O 2 ), organic peroxides (ROOH) and hydroxyl radical (Chin et al, 1994) Mostofa et al, 2009a) Fluorescent dissolved organic matter in the aquatic environments 241 (•OH) by photolysis of CDOM or FDOM in waters (Cooper et al, 1988;Moore et al, 1993;O'Sullivan et al, 2005;Mostofa and Sakugawa, 2009); (iii) Photoinduced production of •OH by the photo-Fenton (Zepp et al, 1992;White et al, 2003) as well as the photoferrioxalate/H 2 O 2 reactions (Safarzadeh-Amiri et al, 1997;Southworth and Voelker, 2003).…”
Section: Biogeochemical Functions Caused By Photochemical and Microbimentioning
confidence: 99%
“…Previous studies have reported the photonitration of phenols by nitrite and nitrate ions that absorb sunlight and generate reactive species and then attack the aromatic ring (Maddigapu et al, 2010;Vione et al, 2007). This process is important for the transformation of phenols in surface waters and produces various nitrophenols, including DCNP (Mack and Bolton, 1999;Minero et al, 2007). In addition, the kinetics of DCNP formation depend on both substraterelated and ecosystem-related variables, especially the chemical composition of the water and sunlight penetration (Loiselle et al, 2009).…”
Section: Introductionmentioning
confidence: 99%